Determinants of Lending Behavior in Nepalese Commercial Banks - Pandeya, Ganga Kumari (Nepalese Journal of Finance, 2024)
The study examines the determinants of lending behavior in Nepalese commercial banks. Loans and advances and credit to deposit ratio are selected as the dependent variables. The selected independent variables are volume of deposit, bank size, liquidity ratio, lending interest rate, inflation rate and cash reserve ratio. The study is based on secondary data of 15 commercial banks in Nepal with 105 observations for the study period from 2015/16 to 2021/22. The data were collected from Banking and Financial Statistics published by Nepal Rastra Bank, publications, website of Nepal Rastra Bank (NRB), Ministry of Finance and annual report of selected commercial banks. The correlation coefficients and regression models are estimated to test the significance and importance of different factors on the lending behavior of Nepalese commercial banks. The study showed that volume of deposit has a positive impact on loans and advances. It means that increase in volume of deposit leads to increase in loans and advances. Likewise, bank size has a positive impact on loans and advances. It means that increase in bank assets size leads to increase in loans and advances. In addition, liquidity ratio has a negative impact on loans and advances. It shows that higher the liquidity ratio, lower would be the loans and advances. In contrast, lending interest rate has a positive impact on loans and advances and credit to deposit ratio. It indicates that increase in lending interest rate leads to increase in loans and advances and credit to deposit ratio. In addition, inflation rate has a positive relationship with loans and advances and credit to deposit ratio. It indicates that increase in inflation rate leads to increase in loans and advances and credit to deposit ratio.